Evaluation of the effect of the feeding regime on the removal of metals and pathogens in microalgae–bacterial systems - Farias, Sarah Lacerda; Ruas, Graziele [UNESP]; Serejo, Mayara Leite; Boncz, Marc Árpád (IWA Publishing, 2023)
Microalgae–bacteria systems are used for the treatment of effluents, using a technology that has stood out with excellent results, as reported in the literature. However, investigating these systems in more depth can improve our understanding of the removal mechanisms for a wide range of existing and emerging pollutants and help improve the guidelines for design and operation, in order to improve the treatment efficiency as well as biomass productivity. This work studied the impact of the feeding regime on the removal of metals and pathogens from primary domestic wastewater in high rate algal ponds (HRAPs). For this, one reactor was fed continuously (HRAP1) while two reactors were fed in semi-continuous mode, during 12 h day-1 (HRAP2) and 0.1 h day-1 (HRAP3). Although removal efficiencies of 82 + 5% for Mn and 90% for E. coli were reached in the semi-continuously fed reactors, there was no significant difference between the conditions studied. On the other hand, for biomass productivity, the semi-continuous feeding regime was more advantageous with a growth of ≈ 22 mg L-1 day-1
Keywords: biosorption; disinfection; E. coli; heavy metals; HRAP; wastewater treatment